Turning Plastic Bags Into Use-Value Goods in Muara Dua Village, Bengkulu City - Hartati, Merri Sri; Ilhami, Mardhiyah Dwi; Nopriyeni, Nopriyeni (Pengabdian: Jurnal Abdimas, 2024)
Of course, plastic waste is still a major problem in maintaining the cleanliness of the local environment. Plastic can be reprocessed into an object that is useful in the future and can be reused in community activities. The danger caused by unprocessed plastic waste can certainly cause damage to the environment. Through the activities carried out in Pagar Dewa Village, Bengkulu City, of course, it can provide a new lesson in terms of understanding and processing plastic waste. Of course, plastic can be reprocessed into a craft, besides that it can also increase the creativity of teenagers in the use and processing of plastic waste. The method of implementing the activities used is socialization and practicum for young mothers and teenagers in Pagar Dewa Village, Bengkulu City in managing plastic waste into crafts and the advantages gained are adding value to creativity. The first stage of activity provides socialization regarding understanding in the form of education to young mothers and teenagers regarding plastic waste processing activities and guides them by teaching them how to process plastic waste so that they can produce creative products and can even increase their finances. The results obtained are in the form of products from the utilization of used plastic into stationery storage which is used for storing stationery items such as pencils, pens and erasers and can also be used for fruit baskets and so on.